Psoriasiform Dermatitis in a COVID-19 Patient - Marlyn Wu; Shereen Teymour; Robin Ashinoff; Hira Ghani (Case Reports in Dermatological Medicine)
Psoriasis is a chronic inflammatory papulosquamous disorder which affects around 2% of the world’s population. A peak exacerbation in psoriatic symptoms was noted during COVID-19 due to lack of access to dermatological care mixed with heightened emotional stress during the pandemic. This case report describes a 52-year-old admitted male patient who sustained a diffuse rash on multiple areas of his body a week prior to testing positive for COVID-19. We explore plausible causes for the occurrence of the rash, discuss our treatment plan, include relevant clinical pictures, and review published literature to examine conditions that present similarly to the rash seen in our patient. It is crucial for dermatologists to be able to discern various systemic manifestations associated with cutaneous lesions, such as the one seen in this patient, in order to make an accurate and prompt diagnosis. A better understanding of the association between COVID-19 infection and psoriasiform lesions is needed for improving the prognostic and therapeutic outcomes in patients.